Industrial-Scale Production and Applications of Bacterial Cellulose - Zhong, Chunyan (Frontiers in Bioengineering and Biotechnology, 2020)
Bacterial cellulose (BC) is a natural nanomaterial synthesized by bacteria. It possesses a unique structure of cellulose nanofiber-weaved three-dimensional reticulated network that awards it excellent mechanical properties, high water holding capability and outstanding suspension stability. It is also characterized with high purity, high degree of crystallinity, great biocompatibility and biodegradability. Due to these advantages, BC has gained great attentions in both academic and industrial areas. This critical review summarizes the up-to-date development of BC production and application from an industrial perspective. Firstly, a fundamental knowledge of BC’s biosynthesis, structure and properties is addressed, and then recent developments in the industrial fermentation of BC are introduced. Subsequently, the latest commercial applications of BC in the areas of food, personal care, household chemicals, biomedicine, textile, composite resin are summarized. Finally, a brief discussion of future development of BC industry is presented at the end.